Detection of geological object boundaries using the gravity tilt derivative method: a case study of the Carpathian foredeep - PETROKUSHYN, Roman; BEZRODNYI, Dmytro; BANCALA, Giuseppe; DE LUCA, Luciana (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2026)
Background. The article presents a methodology and the results of its application for delineating object boundaries based on gravity data analysis. The primary focus is on identifying geological lineaments, such as faults and zones of increased fracturing, which are crucial for understanding the structural and tectonic framework and assessing the geothermal potential of the area. The Carpathian Foredeep was chosen as the study area due to its complex tectonic structure and its potential for geothermal and hydrocarbon resource exploration. Methods. To analyze geological structures, the tilt derivative method of the gravity field (Tilt Derivative) was employed in combination with spectral analysis and Fourier transformation. The methodology includes several steps: calculating the gradient of the gravity field, smoothing, non-maximum suppression, and contour thresholding. This approach ensures high accuracy in determining the boundaries of geological objects and identifying discontinuities in the gravity potential function. The data analysis was conducted using gravity survey results within the Carpathian Foredeep. Results. The application of the methodology allowed for the identification of regional and local lineaments corresponding to faults and zones of increased fracturing. These zones may serve as migration pathways for geothermal waters from deep heated areas to reservoir rocks, enhancing their prospectivity for exploration. A comparative analysis of the obtained results with existing geological maps confirmed the high accuracy of the methods. Additionally, new structures were identified that had not been previously recognized, highlighting the effectiveness of the proposed methodology. Conclusions. The proposed methodology is an effective tool for the detailed delineation of fault and tectonic structures based on gravity data. Its application enables the refinement of the structural and tectonic framework of regions, the identification of new faults and zones of increased fracturing, which are critical for exploring geothermal and hydrocarbon resources. The methodology has broad potential for use in studies of complex geological objects, such as the Carpathian Foredeep, and can significantly improve the efficiency of geological exploration activities.